Pemanfaatan Plastic Canvas sebagai Tas Handmade yang Dikombinasikan untuk Menambah Inovasi Baru pada Produk Handmade - Layla Hanisa; Veronika Mevelia Christine; Zaschia Flanivolya Matulessy; Anggun Pratiwi; Achmad Bagas Djuan R; Irda Agustin Kustiwi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to provide new innovations in handmade products or knitted products. Apart from that, this research also aims to help UMKM in developing their handmade bag business. The methods we use in this activity are research, discussion, training, development and evaluation. The results of this research show an increase in product quality, creativity and sales through digital and offline marketing strategies. Collaboration with partners makes a big contribution, especially in practical training and product marketing. Even though there are challenges such as manual production processes and market competition, innovation and the right marketing strategy can help this product remain competitive and have the opportunity to develop sustainably. We hope that UMKM players can develop the handmade bag or knitted bag business by developing new innovations while maintaining product quality.